Model-based inflation forecasts and monetary policy rules - Raf Wouters; Michel Dombrecht (National Bank of Belgium, 2000)
In this paper, the interaction between inflation and monetary policy rules is analysed within the framework of a dynamic general equilibrium model derived from optimising behaviour and rational expectations. Using model simulations, it is illustrated that the control of monetary policy over the inflation process is strongly dependent on the role of forward looking expectations in the price and wage setting process and on the credibility of monetary policy in the expectation formation process of the private sector. Furthermore, the central bank should take into account a wide variety of indicators in making monetary policy decisions in order to approach the optimal monetary policy rule as closely as possible.
Keywords: 330; Geldpolitik; Glaubwürdigkeit; Inflationsbekämpfung; Erwartungsbildung; Prognoseverfahren; Theorie